Problems of Foreign Language Teaching in Young and School-Age Children - Shokhruh Abdusamadugli Baratov; Saodat Sharipovna Zuparova (Academia One Publishing, 2023)
The given article describes the significant changes in the impact of education on the mental development of young school-age children, and some of the problems they face in understanding themselves, and some problems they face in learning foreign languages and some methodological recommendations for solving them
Keywords: main problems; self-confidence; solution; interactive teaching